2019
DOI: 10.1001/jamanetworkopen.2019.1540
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diabetic Retinopathy and Diabetic Kidney Disease With All-Cause and Cardiovascular Mortality in a Multiethnic Asian Population

Abstract: Key Points Question Among persons with diabetes, are diabetic retinopathy (DR) and diabetic kidney disease (DKD) associated with higher risk of mortality? Findings In this cohort study that included 2964 Asian (Chinese, Malay, and Indian) persons with diabetes followed up for a median of 8.8 years, the presence of DR was associated with higher all-cause mortality independent of presence of DKD. Persons with both DKD and DR had the highest rate of mortality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 24 publications
6
73
0
1
Order By: Relevance
“…In a meta-analysis of studies on type 2 diabetes, Kramer et al 34 showed that DR was associated with 2.41fold increased risk of mortality. In Asians with type 2 diabetes, Sabanayagam et al 35 reported that DR was associated with 1.54-fold increased risk of mortality, and this result is consistent with our own previous study in which we found that DR was associated with 1.58-fold increased risk of mortality in patients without albuminuria. 36 The role of adiposity is ambiguous in patients with DR. 37 DR has been shown to be associated with obesity.…”
Section: Discussionsupporting
confidence: 93%
“…In a meta-analysis of studies on type 2 diabetes, Kramer et al 34 showed that DR was associated with 2.41fold increased risk of mortality. In Asians with type 2 diabetes, Sabanayagam et al 35 reported that DR was associated with 1.54-fold increased risk of mortality, and this result is consistent with our own previous study in which we found that DR was associated with 1.58-fold increased risk of mortality in patients without albuminuria. 36 The role of adiposity is ambiguous in patients with DR. 37 DR has been shown to be associated with obesity.…”
Section: Discussionsupporting
confidence: 93%
“…After primary screening and removing duplicates, 210 potentially eligible articles were selected. After full-text review, 10 eligible cohort studies with 11,239 diabetic patients were finally included in the quantitative synthesis [ 11 – 20 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition to macrovascular disease, diabetes increases the risk of microvascular complications, such as diabetic retinopathy and diabetic kidney disease (DKD). Several lines of evidence suggest that the presence of microvascular disease dramatically increases the risk of macrovascular complications (140)(141)(142). Whether this is due to a shared underlying mechanism or if one complication accelerates the other is unknown.…”
Section: Are Kidney Macrophages In Diabetic Kidney Disease Altered Inmentioning
confidence: 99%